Impact of a high penetration of microgeneration and µGrids in the security of supply - Paulo Moisés A. Costa (2008)
The recent development of the concept ofmicrogrid, associated to the emergent interest in microgeneration,raised a number of challenges regarding the evaluation of thetechnical, economical and regulatory impacts of a highpenetration of this kind of solutions in the power systems. In thispaper, the topic of security of supply is addressed, aiming atevaluating the influence of microgeneration and microgrids in themedium and long term availability of generation to serve theforecasted load. A Monte-Carlo based methodology is used, tocompare the adequacy indices of a base case withoutmicrogeneration with the indices associated to variouspenetrations of different technologies of microgeneration (CHP,PV, wind, etc) and the existence of µGrids.